Window wall - Rawn, Melanie (New York : Tor, 2015)
For nearly two years, Cade has been rejecting his Fae gift, his prescient Elsewhens--simply refusing to see or experience them. But the strain is driving a wedge between him and his theater troupe, Touchstone, and making him erratic on stage and off. It takes his best friend Mieka to bully Cade into accepting the visions again. But when Cade finally looks into the possible futures, he sees a royal castle blowing up, though his vision does not tell him who is responsible. But he knows that if it is in his visions, he can take action to stop it from happening. And when he finally discovers the truth, he takes the knowledge to the only man in the Kingdom who would believe him: his deadly enemy the Archduke.
"A Tom Doherty Associates book."
Keywords: Prophecy -- Fiction; Elves -- Fiction; Wizards -- Fiction; Theatrical companies -- Fiction; Traveling theater -- Fiction; Magic -- Fiction; Fantasy fiction